EFEKTIVITAS MODEL STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) BERBANTUAN MEDIA FLIPBOOK TERHADAP BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS DI SD 2 GETAS PEJATEN - Shovia, Rumaizha; Ismaya, Erik Aditia; Masfuah, Siti (STKIP Persada Khatulistiwa Sintang, 2025)
This study aimed to examine the effectiveness of the Student Teams Achievement Divisions (STAD) model assisted by flipbook media in enhancing fourth-grade students’ critical thinking skills in social science (IPAS) learning. The research employed a quantitative approach with a one-group pretest-posttest design. The subjects were 27 fourth-grade students at SD 2 Getas Pejaten. Data were collected through tests, observations, interviews, and documentation. Data analysis included the Shapiro-Wilk normality test and paired sample t-test using SPSS. The results indicated that the data were normally distributed and there was a significant difference between pretest and posttest scores. The average pretest score was 44.48, which increased to 83.19 in the posttest, with a significance value of 0.000. These findings suggest that the STAD model assisted by flipbook media is effective in improving students’ critical thinking skills.